The Effect of Model Problem Solving on Students’ Problem- Solving Skills Class VII SMPN 34 Padang - Rika Gustia; Ristiono Ristiono; Zulyusri Zulyusri; Heffi Alberida (Universitas Negeri Padang, 2020)
This research has motivated the problem of low students’ problem -solving skills. In the learning process, the teacher rarely trains students’ problem-solving skills and currently Science literacy in Indonesia is low compared to other countries. The results of the preliminary test showed that the average problem-solving skills of students was less than 50%. This study aims to look at the effect of the problem- solving model on the problem-solving skills of grade VII students of SMPN 34 Padang. This type of research is a quasi-experimental design with the Control Group Posttest Only Design. The study population was VII grade students of 34 SMPN Padang in the 2018/2019 academic year. The research sample of students in class VII 4 as the experimental class and VII 5 as the control class. Sampling using a purposive sampling technique. Instruments in the form of observation sheets observation of student activities to obtain data problem-solving skills. Based on the results of the students' problem- solving skills research, the t count 2,24> t table 1,67.The study concluded is that the application of the problem-solving model has a positive effect on the problem-solving skills of grade VII students of SMPN 34 Padang.